2021
DOI: 10.3390/toxics9120346
|View full text |Cite
|
Sign up to set email alerts
|

Protracted Impairment of Maternal Metabolic Health in Mouse Dams Following Pregnancy Exposure to a Mixture of Low Dose Endocrine-Disrupting Chemicals, a Pilot Study

Abstract: Pregnancy, a period of increased metabolic demands coordinated by fluctuating steroid hormones, is an understudied critical window of disease susceptibility for later-life maternal metabolic health. Epidemiological studies have identified associations between exposures to various endocrine-disrupting chemicals (EDCs) with an increased risk for metabolic syndrome, obesity, and diabetes. Whether such adverse outcomes would be heightened by concurrent exposures to multiple EDCs during pregnancy, consistent with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 112 publications
(157 reference statements)
1
4
0
Order By: Relevance
“…It has been claimed that ITT, GTT, and PTT and their AUC are now relatively standard indicators for the detection of the regulation of blood glucose . Similar results indicating that MLT controls glucose homeostasis have been reported in different obesity models. ,,, These data share trends with certain distinctive features of diabetes . Glycemia excursions and diminished glucose regulation could contribute to the propensity for the development of diabetes mellitus .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has been claimed that ITT, GTT, and PTT and their AUC are now relatively standard indicators for the detection of the regulation of blood glucose . Similar results indicating that MLT controls glucose homeostasis have been reported in different obesity models. ,,, These data share trends with certain distinctive features of diabetes . Glycemia excursions and diminished glucose regulation could contribute to the propensity for the development of diabetes mellitus .…”
Section: Discussionsupporting
confidence: 53%
“…Some environmental contaminants (ATZ, bisphenol A, perfluorooctanoic acid, etc.) have been found to contribute to glucose intolerance and digestive disturbances . It has been suggested that the risks of ATZ and abnormal glucose regulation (AGR), fasting glycemia levels (FPG), impaired fasting glucose (IFG), and type 2 diabetes (T2D) could be positively associated …”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue also brings together a set of publications detailing cutting-edge mixture research using both rodent and zebrafish models. Merrill et al, 2021 utilized a mixture of four endocrine-disrupting chemicals (atrazine, bisphenol A, perfluorooctanoic acid, and 2,3,7,8-tetrachlorodibenzo-p-dioxin) that were likely to co-occur in a pregnancy exposure model in mice and compared exposure-induced effects between both pregnant and non-pregnant dams, assessing the impact of pregnancy as a potential non-chemical stressor [ 19 ]. The mixture induced metabolic health effects (e.g., glucose intolerance, increased weight, visceral adiposity, and serum lipids) in the exposed dams, but only in those exposed during pregnancy, supporting the concept of a complex stressor (chemical exposure during a critical physiological window) potentially producing more significant effects than traditional chemical(s) exposure [ 19 ].…”
mentioning
confidence: 99%
“…However, the concept of pregnancy as a sensitive period of health programming also for the pregnant woman is gaining traction 5 . A review by Varshavsky et al 6 highlighted that “the pregnancy exposome may substantially contribute to maternal health risks” and is corroborated by correlate murine model studies 7 . In 2019, the National Institute of Environmental Health Science and the Office of Research on Women's Health issued a related grant opportunity.…”
mentioning
confidence: 99%
“…5 A review by Varshavsky et al 6 highlighted that "the pregnancy exposome may substantially contribute to maternal health risks" and is corroborated by correlate murine model studies. 7 In 2019, the National Institute of Environmental Health Science and the Office of Research on Women's Health issued a related grant opportunity. Seven subsequent projects began in 2020 looking at an array of outcomes-for the pregnant woman, not the developing child-associated with exposures during pregnancy including endocrine function, immune tolerance, cardio-metabolic health, and obesity risk.…”
mentioning
confidence: 99%